Systematic and unsystematic risk determinants of liquidity risk between Islamic and conventional banks - Waemustafa, Waeibrorheem; Sukri, Suriani (EconJournals, 2016)
The fundamental function of banking remains unchanged throughout the the history of banking theory. The management of risk, asset and liability remain the core function of banking. The early signal of banking crisis can be observed from the volatility of liquidity risk. Hence, this study attempted to investigate the influence of external and internal factors affecting liquidity risk of Islamic and conventional banks. This study employs time series regression analysis of Islamic banks and conventional banks from 2000 to 2010. The study found that Islamic banks maintain higher liquidity compared to conventional banks. The multivariate regression analysis shows that four out of fourteen bank-specific factors and one macroeconomic factor significantly influence the liquidity risk of Islamic bank whereas conventional banks show that Five out of thirteen bank-specific factors are significant to liquidity risk.